2011
DOI: 10.5367/te.2011.0028
|View full text |Cite
|
Sign up to set email alerts
|

Crowding-Out Effects of Cruise Tourism on Stay-Over Tourism in the Caribbean: Non-Parametric Panel Data Evidence

Abstract: Based on a non-parametric panel data estimation, this study provides an econometric analysis of the relationship between stay-over and cruise tourism for 15 Caribbean islands over the period 1985-2004. It reveals heterogeneity of tourism flows across different destinations. It also emphasizes the crowding-out effects of cruise tourism on stayover tourism. Using a static Cournot game framework, the authors show that, for most of the destinations, stay-over tourism and cruise tourism are strategic substitutes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…Besides the generic GRI indicators, it is worth mentioning cruises change the character of harbor areas in destinations, often making them unattractive to local citizens (Seidl, Guiliano, & Pratt, 2007) and land-based tourists alike (Klein, 2011). This is especially acute in small destinations where the ratio to cruise passenger per resident is high (Brida & Zapata, 2010) and is causing a "crowding-out trap" of the stay-over tourism (Bresson & Logossah, 2011).…”
Section: Socio-economic Impactsmentioning
confidence: 99%
“…Besides the generic GRI indicators, it is worth mentioning cruises change the character of harbor areas in destinations, often making them unattractive to local citizens (Seidl, Guiliano, & Pratt, 2007) and land-based tourists alike (Klein, 2011). This is especially acute in small destinations where the ratio to cruise passenger per resident is high (Brida & Zapata, 2010) and is causing a "crowding-out trap" of the stay-over tourism (Bresson & Logossah, 2011).…”
Section: Socio-economic Impactsmentioning
confidence: 99%
“…Among all market structure models, oligopoly has attracted the most attention in the literature, such as the studies by Baum and Mudambi (1994) on the UK fully inclusive tour industry, Davies (1999) on the UK hotel industry, Baum and Mudambi (1995) on the resort hotel industry in Bermuda, Bresson and Logossah (2011) on the cruising sector in the Caribbean, and Ciliberto and Tamer (2009) on the American airline industry. In these studies, the common characteristics of oligopoly are identified in tourism markets in which a small number of large firms dominate the markets, which leads to both high market concentration and fixed costs due to entry barriers.…”
Section: The Structure-conduct-performance (Scp) Paradigmmentioning
confidence: 99%
“…These multiplier effects are particularly important for spreading the benefits of Panama's tourism industry to the poor, since many of the poor do not have direct contact with tourists. Moreover, different segments of the tourism sector may act as substitutes, and tourism activities with insignificant local linkages may crowd out other forms of tourism with higher potential local benefits, such as might be the case with cruise ship versus overnight stay tourism in the Caribbean (Bresson and Logossah, ).…”
Section: Results: Province‐level Tourism Spending Growth Linkages Anmentioning
confidence: 99%